Electric power communication network service importance evaluation method for quantum key application - Guochun LI; Suxiang ZHANG; Wei DENG; Zhuozhi YU; Yefeng ZHANG; Yukun ZHU (Dianxin kexue)
With the expansion of the power grid and the increase of the complexity of the power system, the power grid has more stringent requirements for the security of the services transmission. In the secondary protection system of power systems, traditional encryption devices use symmetric encryption algorithms to add and decrypt communication data. Quantum keys have extremely high security. Applying the quantum keys to the power communication network encryption devices can greatly improve the security of service transmission. The quantum key resources generated by the existing quantum key distribution devices is limited, and it is difficult to ensure that all power services data are encrypted and transmitted. Therefore, it is necessary to prioritize the confidential transmission of important services by establishing appropriate evaluation methods for services importance. A relative importance matrix based on the transmission performance indicators of each service was built under the background of quantum communication, so as to obtain the importance of the power communication network business, and to carry out subsequent quantum key application strategy research.